ICT in the Research Workflow Survey Report - Chan, Janice; Green, Peter; Buttsworth, Andrew; Pedrotti, David (Curtin University, 2019)
Curtin University conducted a survey in 2012 to capture the ICT needs of researchers from all fields of research. The survey was a collaboration between the University Library, Research Office at Curtin, and Digital and Technology Solutions. In 2019 the eResearch Special Interest Group ran the survey again to compare the current state of ICT needs of researchers with 2012 and inform University planning and support for researchers. This report covers results and analytical narratives from both completed and partially completed surveys. Where there is notable difference in the responses between HDR students and staff, breakdown of responses by role are included. This report also includes findings from the 2012 report for comparison where applicable.